High‐resolution intravascular MRI‐guided perivascular ultrasound ablation. Issue 1 (11th August 2019) - Liu, Xiaoyang; Ellens, Nicholas; Williams, Emery; Burdette, Everette C.; Karmarkar, Parag; Weiss, Clifford R.; Kraitchman, Dara; Bottomley, Paul A.
Abstract : Purpose: To develop and test in animal studies ex vivo and in vivo, an intravascular (IV) MRI‐guided high‐intensity focused ultrasound (HIFU) ablation method for targeting perivascular pathology with minimal injury to the vessel wall. Methods: IV‐MRI antennas were combined with 2‐ to 4‐mm diameter water‐cooled IV‐ultrasound ablation catheters for IV‐MRI on a 3T clinical MRI scanner. A software interface was developed for monitoring thermal dose with real‐time MRI thermometry, and an MRI‐guided ablation protocol developed by repeat testing on muscle and liver tissue ex vivo. MRI thermal dose was measured as cumulative equivalent minutes at 43°C (CEM43 ). The IV‐MRI IV‐HIFU protocol was then tested by targeting perivascular ablations from the inferior vena cava of 2 pigs in vivo. Thermal dose and lesions were compared by gross and histological examination. Results: Ex vivo experiments yielded a 6‐min ablation protocol with the IV‐ultrasound catheter coolant at 3‐4°C, a 30 mL/min flow rate, and 7 W ablation power. In 8 experiments, 5‐ to 10‐mm thick thermal lesions of area 0.5‐2 cm 2 were produced that spared 1‐ to 2‐mm margins of tissue abutting the catheters. The radial depths, areas, and preserved margins of ablation lesions measured from gross histology were highly correlated (r ≥ 0.79) with those measured from the CEM43 = 340 necrosis threshold determined by MRI thermometry. The psoas muscle was successfully targeted in the 2 live pigs, with the resulting ablations controlled under IV‐MRI guidance. Conclusion: IV‐MRI‐guided, IV‐HIFU has potential as a precision treatment option that could preserve critical blood vessel wall during ablation of nonresectable perivascular tumors or other pathologies.